THE RECENT EVOLUTIONS AND PERFORMANCE OF MICROFINANCE INDUSTRY IN INDIA - KAPOOR, BHISHAM; TYAGI, EKTA (International Journal of Psychosocial Rehabilitation, 2020)
The present paper highlights the evolutions of microfinance & evaluates their performance. Microfinance is neither a new idea nor a recent development. Self employed women’s association (SEWA) was the first initiative to introduce microfinance in India and it was established in Ahmedabad. Microfinance is an important tool for ending poverty. It plays a vital role in revitalizing the global economy and creates a financial marketplace for developing countries like India. there are mainly two types of delivery models of Microfinance in India that that link formal financial sector with low income household lending in India, namely SHG and MFI bank linkage programme. The present study is based on secondary data. The relevant data has been collected from National Bank for Agriculture and Rural Development (NABARD) (Status of microfinance in India report). The study revealed that the number of SHGs and MFIs availing loans from banks during the year 2015 to 2019. The SHG-MFIs and bank linkage is an effective way for people in need to easily access financial services.